Asksia AI LOGO

Sia

1808673598's Question
Biology
Posted 4 months ago

6

4(a) (i) Solve 2e12y=3e3y+22 \mathrm{e}^{1-2 y}=3 \mathrm{e}^{3 y+2}. Give your answer in exact form.
Sign in to unlock the answer
Answer from Sia
Posted 4 months ago
To solve the equation 2e12y=3e3y+22 e^{1 - 2y} = 3 e^{3y + 2}, we can start by simplifying it step by step.

1. 
Rearranging the equation
: Divide both sides by e12ye^{1 - 2y}:
   2=3e3y+2/e12y
   2 = 3 e^{3y + 2} / e^{1 - 2y}
   
   This simplifies to:
   2=3e(3y+2)(12y)=3e5y+1
   2 = 3 e^{(3y + 2) - (1 - 2y)} = 3 e^{5y + 1}
   

2. 
Isolating the exponential
: Now, we can isolate e5y+1e^{5y + 1}:
   e5y+1=23
   e^{5y + 1} = \frac{2}{3}
   

3. 
Taking the natural logarithm
: To solve for yy, take the natural logarithm of both sides:
   5y+1=ln(23)
   5y + 1 = \ln\left(\frac{2}{3}\right)
   

4. 
Solving for \(y\)
: Now, isolate yy:
   5y=ln(23)1
   5y = \ln\left(\frac{2}{3}\right) - 1
   
   y=ln(23)15
   y = \frac{\ln\left(\frac{2}{3}\right) - 1}{5}
   

So, the exact form of the solution is:
y=ln(23)15
y = \frac{\ln\left(\frac{2}{3}\right) - 1}{5}


If you have any further questions or need clarification on any steps, feel free to ask!

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Unlock Smarter Learning with AskSia Super!

Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.

30% higher accuracy than GPT-4o
Entire learning journey support
The most student-friendly features
Study Other Question